Hydrate Phase Equilibria for Methyldiethanolamine and Empirical Modeling for Prediction - Alef, K.; Iglauer, Stefan; Gubner, Rolf; Barifcani, Ahmed (American Chemical Society, 2018)
© 2018 American Chemical Society. The issue of gas hydrates in gas pipelines is commonly addressed by injecting hydrate inhibitors at the well heads. Alongside these inhibitors, other chemical additives are also injected to address various concerns such as to reduce the risk of corrosion and scaling. However, it is not clear how the combined chemical cocktail affects gas hydrate formation over a wide pressure range. Monoethylene glycol (MEG) and methyldiethanolamine (MDEA) are common chemicals that are usually used as part of hydrate inhibition and corrosion control programs respectively. Thus, in this study, the methane hydrate inhibition performance of MDEA in the presence and absence of MEG was assessed. The study produced new hydrate phase equilibria data at a high pressure range, suggesting MDEA performs as a thermodynamic hydrate inhibitor and thus enhances the hydrate inhibitory performance of MEG. Furthermore, because there does not appear to be any flow assurance prediction software that has the capability to simulate the effect of MDEA on hydrate formation, an algorithm that can accurately predict the equilibrium temperature of aqueous MDEA solutions with and without MEG was developed. The algorithm is based on the empirical modeling of the experimental data obtained in this study. This work will thus aid in the industrial application of hydrate inhibitors and improve gas hydrate prevention in production pipelines.